Disseminated cryptococcosis and anti‐granulocyte‐macrophage colony‐stimulating factor autoantibodies: An underappreciated association. Issue 6 (5th February 2021) - Viola, George M.; Malek, Alexandre E.; Rosen, Lindsey B.; DiNardo, Andrew R.; Nishiguchi, Tomoki; Okhuysen, Pablo C.; Holland, Steven M.; Kontoyiannis, Dimitrios P.
Abstract: The development of disseminated cryptococcosis has historically occurred in patients living with advanced human immunodeficiency virus or other immunosuppressive conditions affecting T‐cell function. Recently, patients with anti‐cytokine neutralising autoantibodies have been recognised to be at risk for disseminated infections by opportunistic intracellular pathogens, including Cryptococcus species. Herein, we present a previously healthy 26‐year‐old man who was evaluated with disseminated cryptococcosis involving the bone, lung, mediastinum and brain. The patient's serum cryptococcal antigen titres were >1:1, 100, 000, and evaluation for an underlying immunodeficiency revealed high titres for anti‐granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) autoantibodies. We also review the literature of all published cases of disseminated cryptococcosis associated with the presence of anti‐GM‐CSF autoantibodies. Clinicians should have a heightened awareness of anti‐cytokine autoantibodies in patients without a known immunodeficiency and development disseminated infections by opportunistic intracellular pathogens.